5(2x+3)+2(5x-1)=37

Simple and best practice solution for 5(2x+3)+2(5x-1)=37 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2x+3)+2(5x-1)=37 equation:


Simplifying
5(2x + 3) + 2(5x + -1) = 37

Reorder the terms:
5(3 + 2x) + 2(5x + -1) = 37
(3 * 5 + 2x * 5) + 2(5x + -1) = 37
(15 + 10x) + 2(5x + -1) = 37

Reorder the terms:
15 + 10x + 2(-1 + 5x) = 37
15 + 10x + (-1 * 2 + 5x * 2) = 37
15 + 10x + (-2 + 10x) = 37

Reorder the terms:
15 + -2 + 10x + 10x = 37

Combine like terms: 15 + -2 = 13
13 + 10x + 10x = 37

Combine like terms: 10x + 10x = 20x
13 + 20x = 37

Solving
13 + 20x = 37

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + -13 + 20x = 37 + -13

Combine like terms: 13 + -13 = 0
0 + 20x = 37 + -13
20x = 37 + -13

Combine like terms: 37 + -13 = 24
20x = 24

Divide each side by '20'.
x = 1.2

Simplifying
x = 1.2

See similar equations:

| 7e+23=3e+(-7)+(-5) | | -42-9x+2x=49 | | .5(x+12)=4x-1 | | (0.5x-1)(4x+2)= | | 12x+26=4x+210 | | 5(x-2)=3(2x-4) | | 4a=1.44 | | 4e+6-2e-12=18 | | 2x(x)=48 | | 43x-4+1=2x-5+5x | | 20-x=330 | | -5+e+(-3)+11=4+21 | | (15)3/5= | | x-18y=19fory | | 4a+3=93 | | -26+x=-39+6x | | 2b-16=12 | | .75e^2x=.5 | | -5x=14(2x) | | X+3x+2x=x+3 | | Log(2x)+log(X)=7 | | 2(x-1)=3x-7-x | | 9(v+3)=6v+15 | | 150m-75m+52250=56375-200m | | 2e-e=3e+4 | | x^33-3=-3x^2+8x | | 3(x+3)=7x+2-4x+7 | | 45+65x=50 | | 4x^2-27x+29=-3x+2 | | 44x+1=45 | | 2.25x+3=4.125 | | 25%d=4 |

Equations solver categories